Poly(D,L-Lactic Acid) Nanoparticle Size Reduction Increases Its Immunotoxicity - Da Silva, Jessica; Jesus, Sandra; Bernardi, Natália; Colaço, Mariana; Borges, Olga (Frontiers in Bioengineering and Biotechnology, 2019)
Polylactic acid (PLA), a biodegradable and biocompatible polymer produced from renewable resources, has been widely used as a nanoparticulate platform for antigen and drug delivery. Despite generally regarded as safe, its immunotoxicological profile, when used as a polymeric nanoparticle (NP), is not well-documented. Thus, this study intends to address this gap, by evaluating the toxicity of two different sized PLA NPs (PLAA NPs and PLAB NPs), produced by two nanoprecipitation methods and extensively characterized regarding their physicochemical properties in in vitro experimental conditions. After production, PLAA NPs mean diameter (187.9 ± 36.9 nm) was superior to PLAB NPs (109.1 ± 10.4 nm). Interestingly, when in RPMI medium, both presented similar mean size (around 100 nm) and neutral zeta potential, possibly explaining the similarity between their cytotoxicity profile in PBMCs. On the other hand, in DMEM medium, PLAA NPs presented smaller mean diameter (75.3 ± 9.8 nm) when compared to PLAB NPs (161.9 ± 8.2 nm), which may explain its higher toxicity in RAW 264.7. Likewise, PLAA NPs induced a higher dose-dependent ROS production. Irrespective of size differences, none of the PLA NPs presented an inflammatory potential (NO production) or a hemolytic activity in human blood. The results herein presented suggest the hypothesis, to be tested in the future, that PLA NPs presenting a smaller sized population possess increased cytotoxicity. Furthermore, this study emphasizes the importance of interpreting results based on adequate physicochemical characterization of nanoformulations in biological medium. As observed, small differences in size triggered by the dispersion in cell culture medium can have repercussions on toxicity, and if not correctly evaluated can lead to misinterpretations, and subsequent ambiguous conclusions.